Experimental and Numerical Research on Cylindrical Tubes under Outer Cylindrical Explosive Waves. (4th June 2017) - Yaguang, Sui; Dezhi, Zhang; Shiying, Tang; Bo, Chen
Abstract : Cylindrical explosive loading has an important application in explosive working, researching on weapon damage, and explosive-driving load. This study uses experimental and numerical methods to study the response of long and thin tubes when subjected to cylindrical explosive loading. The flake-like charge and multipoint initiation technique were adopted to load cylindrical explosive waves. Experimental results showed that the method could produce uniform deformation in certain parts of the long tube, but partial spall injuries occurred after the explosion. The macroscopic and microscopic deformation of tubes were analyzed. Numerical simulations were conducted to investigate the detailed response of the tube subjected to a cylindrical explosive wave. The results indicate that the collision of explosive waves brought inconsistencies in pressure and velocity. The pressure and velocity in the collision region were significantly higher than those of other parts, which caused the collision region to be easily damaged.